Relationship Between Content Characteristics and Audience Responses: A Large-scale Investigation of Text (News) and Video (TV Advertising) - (:unkn) unknown (My University, 2023)
Content play a vital role in modern marketing strategies, serving as powerful tools to engage and influence target audiences. In an era of information overload and short attention spans, compelling and valuable content has become essential for capturing and retaining consumer interest. This dissertation investigates how the characteristics of two different forms of content – written text and video – affect their audiences’ engagement with them.Essay 1 examines the relationship between a news article's organization and its expositional characteristics such as writing style, topic, and authorship on readers’ engagement with the article. Engagement is operationalized as the number of comments from readers on the article. The impact of comments on news articles is crucial for news publishers, as it influences audience engagement and revenue generation. Using a corpus of over 41,000 articles from eight digital news sites, various methods, including rule-based and machine learning approaches, are employed to measure emotions, concreteness, tone, verbosity, and author's Twitter audience. The findings reveal associations between comment volume and factors like emotions, verbosity, expositional characteristics, and author engagement on social media. Additionally, the study identifies variations in comment volume based on different topics. Essay 2 investigates the influence of advertising content on consumer responses to price increases in the context of inflation in the United States. Analyzing a comprehensive dataset of 2,435 television advertisements across various product categories and brands, the study employs a hierarchical model to explore the impact of advertising content on consumer intent to purchase during price increases. The findings reveal that energetic content significantly drives consumer purchasing behavior. We also find that funny inspiring, and nostalgic ads have no discernible effect, except for nostalgic ads which show an increased impact on purchase intent during inflationary periods. Furthermore, less affluent consumers tend to purchase more utilitarian products following inflation. These insights have practical implications for companies navigating inflation-related challenges and can inform the development of effective marketing strategies to adapt to evolving consumer behavior. Essay 3 explores the interplay between inflation, brand positioning, and ad features, within the context of a rapidly changing economic landscape marked by the highest inflation rates since 1982. Our analysis of over 2,000 video advertisements aired for about a million times reveals a distinct shift in consumer viewing behavior during these inflationary periods. Notably, we find that value brands hold viewers' attention better, although value brands benefit more from less emotional content. These insights offer key strategic implications for marketers navigating an inflationary economy.